(untitled) (Research, Society and Development, 2021)
Introduction: Abdominal trauma has high morbidity and mortality, and it is essential for its diagnosis would be made faster to minimize injuries. In order to achieve the quality of support protocols for the traumatized victim, programs are used, using the severity indices. Objective: To assess the profile of victims of abdominal trauma, with or whithout politrauma, using the severity indices TRISS and TRISS-like, attended in a critical axis of an urgency and emergency hospital in the state of Sergipe. Methods: Cross-sectional, prospective observational study, with a quantitative approach to victims of abdominal trauma. It was used an instrument of its own elaboration, having as a base or instrument of Domingues (2013), that provides objective questions with physiological and sociodemographic data on the topography and clinical information of the study. Results: Sample of 42 patients, obtained a mean of 33.1 years, with 81% being male and 19% female, whereas 61.9% were affected by transport with a difference between mechanisms. blunt 66.7% and penetrating mechanism 33.3%. All the accidents 100% received pre-hospital care, being that 28.6% died and 50% required ICU care. The TRISS-like group has a lower probability of survival than the TRISS (7.1% vs 97.2%). Conclusion: Due to the predominant cause of abdominal trauma, there was an accident of transport as a contusive mechanism prevailing, mostly homens, adults, with an average age of 33.1 years. All the victims receive pre-hospital support and a considerable death tax.